ANALYSIS OF CATTLE WASTE WHICH HAS THE POTENTIAL TO CONTAMINATE THE ENVIRONMENT AND SPREAD DISEASES IN SOCIETY - Suada, I Ketut; Tenaya, I Wayan Masa (Buletin Veteriner Udayana, 2023)
Cattle farm waste is a source of environmental pollution and a source of disease transmission in society. The emergence of environmental pollution from a farm is mostly caused by livestock waste not being handled properly. The aims of this study were to analyze pollutant elements and the potential for the spread of disease to the community. This study used observational and purposive sampling methods, namely cattle ranch waste samples taken from four traditional cattle groups in South Gianyar. A total of one liter of samples was collected from each group and brought to the Veterinary Public Health Laboratory, Udayana University for analysis. The content of Total Suspended Solid (TSS), Ammonia, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Coliform and E. coli were analyzed using the methods of Gravimetric, Spectrophotometer, Winkler, Titration-spectrophotometer, and Most probable number (MPN ) respectively. The results showed that the value of TSS were 26.75 mg/L, ammonia 7.86 mg/L, BOD5 171.817 mg/L, COD 605.675 mg/L, pH 8.075, Coliform 22 million/100 ml, and E. coli was 20 million/100ml. In conclusion, the cattle farm waste in the current study had the potential to cause environmental pollution and infectious disease to society, contained exceeded the quality standards parameters for BOD5, COD, Coliform, and E. Coli and the bacteria have a potential to cause infectious disease in the community. It was recommended to manage and treat the cattle waste properly based on the recommended breeding practice, to minimize its impact on the environment and public health.